2019
DOI: 10.5817/cp2019-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Do men post and women view? The role of gender, personality and emotions in online social activity

Abstract: According to Nadkarni and Hofmann’s model (2012), a major motivator of social networking sites (SNS) use is the need to belong, i.e., the basic drive to form and maintain relationships. This need can be fulfilled through two kinds of belongingness-related behaviours: information-seeking (using SNS to learn about others) and communication (using SNS to communicate with others). The present study aimed at examining the role of gender, personality traits and emotional competence on each of these two belongingness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
5
9
0
Order By: Relevance
“…To establish to what degree inhibition and demographic features impact public SNSactivity, we performed another regression analysis (Table 4). Being male is the only demographic feature with a significant positive relationship with public SNS-activity in all the models (0.074-78), which supports earlier research that has found that men use SNS to express their opinions more often than women (Rollero et al, 2019). Surprisingly, Social discomfort, the factor that explained most variance (Table 2), is found not to significantly impact public SNS-activity (Table 4, Model 2).…”
Section: Resultssupporting
confidence: 83%
“…To establish to what degree inhibition and demographic features impact public SNSactivity, we performed another regression analysis (Table 4). Being male is the only demographic feature with a significant positive relationship with public SNS-activity in all the models (0.074-78), which supports earlier research that has found that men use SNS to express their opinions more often than women (Rollero et al, 2019). Surprisingly, Social discomfort, the factor that explained most variance (Table 2), is found not to significantly impact public SNS-activity (Table 4, Model 2).…”
Section: Resultssupporting
confidence: 83%
“…Possible explanations include the fact that all of the research team members were women and that apparent gender differences in e.g. online social activity [70] may have been at play. This study analyzed participant experiences with peer support groups that were part of a larger, complex intervention that included multiple online resources as an adjunct to ongoing care.…”
Section: Limitationsmentioning
confidence: 99%
“…Several recent studies have shown that Social Network Sites (SNSs) have a significant influence on young women's body image [5][6][7][8]. SNSs have become the most commonly accessed websites on the Internet [9] and their use, as the main channel for social interaction [10], is constantly growing among young adults. Active users on social networks are over 3 billion and 35 million are Italians [11].…”
Section: Introductionmentioning
confidence: 99%